The Role of Art Education in Safeguarding Intangible Cultural Heritage in Secondary Technical and Vocational Colleges - Li Xingyun; Ima Widiyanah; Mohammad Syahidul Haq (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
Intangible cultural heritage (ICH) requires sustainable pathways of transmission, yet the educational role of art education in supporting ICH safeguarding in secondary technical and vocational colleges remains insufficiently clarified. This study aims to examine how students perceive the role of art education in safeguarding ICH within a vocational college context. A quantitative, descriptive, exploratory survey was conducted using a 30-item questionnaire on a five-point Likert scale, administered to 36 students from Guangdong Huali Technician College. Data were analyzed using descriptive statistics and Cronbach’s alpha. The overall mean score was 4.124 (SD = 0.767), with acceptable internal consistency for the overall instrument (alpha = 0.749), indicating generally positive student perceptions. At the dimension level, the highest mean score was observed for Pathways: Curriculum and Faculty (4.256), followed by Role of Art Education (4.214), while ICH Status and Challenges recorded the lowest, though still positive, mean (4.006). The highest item-level support concerned regularly inviting ICH inheritors for teaching and practice, whereas comparatively lower agreement was observed across several challenge- and integration-related items. Overall, the findings suggest that students perceive art education as a meaningful pathway for safeguarding ICH, particularly through curriculum integration, pedagogical support, and practice-based cultural engagement. However, the evidence should be interpreted as preliminary and perception-based, since the study draws on student responses from a single institutional setting rather than direct observation of educational practice or safeguarding outcomes.